Evaluation of Bacterial Isolates of Pus and Their Antimicrobial Sensitivity Pattern - Vijay Kumar; Ranjan Kumar Srivastava; S. N. Singh (Asian Journal of Medical Research, 2021)
Background: Antimicrobial resistance leads to increase in morbidity, mortality, prolonged hospitalization and huge economic burden on the society. Therefore we need to know the changing pattern of antimicrobial resistance. This study was done to evaluate the bacteriological profile and their sensitivity pattern of pus culture isolates at Patna Medical College and Hospital Bihar. Subjects and Methods: This retrospective study included 213 pus samples collected from patients attending OPD and IPD of different departments of the hospital, presenting pus discharge over a period of 12 months from April 2019 to March 2020. Standard procedure was done for isolation of bacteria from the pus samples and their sensitivity was done using different antibiotics. Results: Out of 213 pus samples 134 (62.9%) were found culture positive in which 128 showed single type of isolate and six with two isolates. Rest 76(37.1%) showed no growth. Staph aureus was found the most common isolate 43 (30.71%) followed by E. coli 32(22.86%), Streptococcus pyogenes 21(15%), Klebsiella 18(12.86%), Pseudomonas 15 (10.71%) and Proteus 11(7.86%) in decreasing order. Increased resistance to commonly used antibiotics was seen. Conclusion: This study evaluates the major pus isolates and their sensitivity pattern. Most of the isolates has shown resistance to the commonly used antibiotics showing improper or misuse of antibiotics. So culture and sensitivity of each and every pus sample is extremely recommended for proper treatment and prevent resistance based complications.